(untitled) (Research, Society and Development, 2024)
Objective: This study aims to analyze blood donation candidates’ clinical and epidemiological profiles in Northern Minas Gerais, Brazil, from 2019 to 2022. Methods: We retrospectively searched clinical and epidemiological profiles in the donor data from Montes Claros’ Hemotherapy Center/ Hemominas Foundation from January 2019 to December 2022. Clinical and epidemiological variables were assessed using a blood bank database. Main Results: Of the 81,195 donation candidates, the majority were female, over 29 years old, repeat donors, and replacement donations. Among them, 18.96% were deemed ineligible, with the majority being female, over 29 years old, repeat donors, and replacement donations. Key causes of ineligibility included STD-risk behavior, anemia, hypertension, and Chagas disease. Women showed higher rates of anemia, hypotension, and Chagas disease, while men had more STD-risk behavior, hypertension, alcoholism, and drug use. Among eligible donors, 2.43% had serological ineligibility, notably for hepatitis B, syphilis, and hepatitis C. Conclusion: The frequency of female and repeat donors in Montes Claros was higher than the national average, with disparities in ineligibility between genders and a possible higher prevalence of syphilis and Chagas disease in the local population.